Enhancing Observability in Distributed Environments through AI: A Structured Overview - Abhishek Walia, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article provides a comprehensive overview of how Artificial Intelligence (AI) is revolutionizing observability in distributed environments. It explores the diverse applications of AI in enhancing system monitoring, management, and maintenance across complex, interconnected IT infrastructures. The article delves into key areas where AI makes significant contributions, including intelligent monitoring, advanced anomaly detection, sophisticated data correlation across systems, predictive maintenance, automated remediation, and continuous improvement. By examining these aspects, the article demonstrates how AI-driven observability solutions are addressing current challenges in managing distributed systems while also paving the way for more resilient, efficient, and adaptive IT environments. The discussion encompasses various AI techniques and models, such as machine learning algorithms, neural networks, and time-series analysis methods, illustrating their practical applications in improving system performance, reducing downtime, and optimizing resource utilization. Ultimately, this article underscores the transformative potential of AI in observability, highlighting its role in enabling proactive, scalable, and intelligent management of distributed systems in an increasingly digital world.
Keywords: AI Observability; Distributed Systems; Predictive Maintenance; Automated Remediation; Anomaly Detection